Perlindungan Hukum terhadap Hak-hak Masyarakat Atas Tanah Akibat Alih Fungsi Lahan untuk Proyek Strategis Nasional dan Pertambangan di Kabupaten Halmahera Timur - Ardiansyah Madjid; Siti Barora Sinay Siti; Nam Rumkel (JURNAL HUKUM PELITA, 2025)
This study aims to analyze the legal protection of community rights to land due to land conversion for National Strategic Projects (PSN) and mining in East Halmahera Regency, North Maluku, from the perspective of agrarian reform. The method used is empirical law (non-doctrinal legal research) qualitative-descriptive approach. Data through interviews with communities, traditional leaders, local governments, and literature studies on primary, secondary, and tertiary legal materials. Research shows that land conversion for PSN and mining causes agrarian conflicts, inequality in land distribution, and threats to local food security. Although spatial planning policies include the principles of justice and ecological sustainability, their implementation has not optimally protected people's rights. Agrarian reform as an instrument of land redistribution and legal protection has not been fully implemented, as can be seen from the low level of land certification and the lack of community participation in decision-making. This research underlines the need for preventive and repressive legal protection, policy synchronization, and increasing the role of the state in ensuring agrarian justice